Employment and Equilibrium - Lerner, Abba P.; Pigou, A. C. (The Review of Economics and Statistics, 1942)
VOLUME 1 Introduction D. Collard Principles and Methods of Industrial Peace, 1905, 260pp Economic Science in Relation to Practice, 1908, 32pp VOLUME 2 Wealth and Welfare, 1912, 524pp VOLUME 3 Economics of Welfare [1920] 1932 4th ed., 868pp VOLUME 4 Unemployment, 1914, 258pp The Political Economy of War, [1921] 2nd ed., 1940, 176pp VOLUME 5 Essays in Applied Economics, 1923, 205pp VOLUME 6 Industrial Fluctuations, [1927] 2nd ed., 1929, 447pp VOLUME 7 A Study in Public Finance, [1928] 3rd ed., 1947, 303pp VOLUME 8 The Theory of Unemployment, 1933, 344pp VOLUME 9 The Economics of Stationary States, 1935, 337pp VOLUME 10 Employment and Equilibrium, [1941] 2nd ed., 1949, 293pp VOLUME 11 Income: An Introduction to Economics, 1946, 125pp Income Revisited, 1955, 94pp VOLUME 12 Aspects of British Economic History 1918-1925, 1947, 259pp VOLUME 13 Keynes General Theory, 1950, 77pp Alfred Marshall and Current Thought, 1953, 92pp VOLUME 14 Essays in Economics, 1952, 247pp